Pencegahan Stunting melalui Transformasi Layanan dan Edukasi Kesehatan - Rahmawati, Anis; Inderasari, Elen; Ananto, Arif; Cahyarani, Chairunnisa Lintang; Setiawan, Muhammad Alvian Putra; Puspitasari, Nisa Indah; Hanafi, Dzulekha Isnawa Arpiya; Fatmi, Karisma Nabila; Aulia, Zeniar Nur; Setyaningrum, Rahmada Fitradewi; Nagari, Gandhi Putri Setya; Choirurrohim, Anisa; Tibyan, Imam Muhijuddin (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Stunting Nutritional challenges and low health literacy in rural areas remain critical public health concerns, including in Mireng Village, Trucuk District, which exhibits a potential risk of stunting. This community service program was designed to enhance the understanding of pregnant women, mothers of toddlers, and posyandu cadres regarding stunting prevention. The activities were implemented using the Asset-Based Community Development (ABCD) approach, leveraging local potentials through participatory stages of planning, implementation, and reporting. The program encompassed educational sessions, awareness campaigns, and direct assistance in Mireng Lor and Pager hamlets. The educational content covered the definition, causes, and prevention strategies for stunting, including the application of healthy kitchen practices. The outcomes demonstrated an improvement in participants’ knowledge and awareness of balanced nutrition, exclusive breastfeeding, and growth monitoring during the First 1,000 Days of Life. The application of the Health Belief Model and community-based intervention principles further strengthened community involvement and cross-sector collaboration, fostering sustainable efforts to reduce stunting prevalence at the village level.